Suggestion for Objective Evaluation of Comparative Pulse Diagnosis - Jun-Sang Yu (Korean Pharmacopuncture Institute, 2024)
Objectives: Pulse is a method of Korean medicine diagnosis and is an important clue to detect the organs, nature, and progress of the disease. Pulse examination is included in the basic examination of Korean medicine doctors, but there is no standardized method for diagnosing pulse although the types and methods of the pulse taking are briefly described in the literature, making it difficult to spread the examination method. In this regard, I would like to propose an objective evaluation method.Methods: Although the importance of pulse examination and the method of pulse examination are known in the literature, it is difficult for undergraduate students or inexperienced Korean medicine doctors to access it, so in this paper a method of marking the size of the pulse power in the blank space for objective evaluation was devised and presented.Results: The size of the pulse power should be indicated using the 1-cell, 3-cell, or 5-cell method according to the left and right wrists and the cun, guan and chi on both sides.Conclusion: The method of pulse diagnosis is an important diagnostic method as a verification process for making a Korean medical diagnosis. The remaining Korean medicine diagnostic methods, including pulse diagnosis, also need to undergo objectification. It is believed that the objectification of these diagnostic methods will lead to an improvement in the treatment rate of Korean medicine.